From war to peace: women weaving the peace places of intervention: Colombia - Perú - Rodríguez Vásquez, Angélica María (2017)
This paper is the result of a five-year investigation. It was made to understand roles that women play in both war and peace in Colombia. They are analyzed as participants in both constructs, war and peace, but also as political subjects that promote social transformation, recognizing in this effort the role they play as journalists in the media, in the duty of generating public opinion that strengthens the processes of women’s empowerment in the search for new states of peace in equity, and the reconstruction of the social frame in territories. The methodology is applied in two countries: Colombia and Peru. In Colombia, interviews are held in territories such as Arauca, Caquetá, Meta, Putumayo and Tolima, plus the systematization of testimonies that are gathered in the framework of meetings in which insurgent women (linked to armed groups) and women victims of the armed conflict participated together, with the support of the Foundation Al Derecho. The second application space in Peru is the San Martin region in Moyobamba, plus field notes in meetings with journalists in Cajamarca and Huacho, and notes from the X Meeting of Women Journalists (Lima-Peru).